A study to assess availability of basic infrastructure of anganwadi centers in a rural area - Debata, Ipsita; P., Anand; T. S., Ranganath (International Journal Of Community Medicine And Public Health, 2017)
Background: The integrated child development service (ICDS) was launched on 2nd October, 1975 as an effort to meet the holistic needs of children below 6 years, adolescent girls, expectant and nursing mothers through the network of anganwadis. Purpose of the study was to assess the availability of basic infrastructure for AWCs under ICDS. Methods: This cross-sectional study was conducted in 21 AWCs in Sondekoppa area, rural field practice area of Bangalore medical college and research institute, Bangalore, India. Results: All anganwadi centers were found to be located within the village locality, favouring easy access for the beneficiaries. 17(81%) AWCs were functioning in government allotted buildings. Compound wall or fence all around the anganwadis were found to be present in only 10 (47.6%) centers. Toilet facilities were found to be present in 12(57.1%) centers. When cleanliness of room and kitchen was assessed, it was found to be good in 13 (61.9%) centers. Assessment of area surrounding the anganwadi centers revealed that 12 (52.1%) centers were free from any nuisance causing factors around. Conclusions: Since anganwadi centre is nodal point for service delivery under ICDS programme, infrastructures like toilet facilities were found to be present in 57.1%, cleanliness of room and kitchen was assessed, it was found to be good in 61.9%.